The impact of social media on human interaction in an organisation based on real-time social media data - Syed Ahmad, Sharifah Sakinah; Shaik Osman, Anis Naseerah; Basiron, Halizah (Inderscience Enterprises Ltd., 2019)
The growth of online social networks around the world has created a new place of interaction and communication among people. Individuals can share their knowledge, opinions, and experiences with one another through the features provided where it gives an impact on people's behaviour in terms of interaction, communication and decision making. Twitter is one of the examples of social media provider that empowers users to send and read short messages called 'tweets'. By trying to connect to the outside world, the user would probably disconnect with people around them and this will also affect the human interaction in an organisation. This research offers possible insights for the organisation to identify the pitfalls and opportunity that lies in the new digital human interaction era. This research will attempt to discuss these issues drawing from social media interaction on physical/digital interactions based on data science approach.